2018
DOI: 10.1007/s11606-018-4444-4
|View full text |Cite
|
Sign up to set email alerts
|

Pay-for-Performance and Veteran Care in the VHA and the Community: a Systematic Review

Abstract: The evidence to support the effectiveness of P4P on Veteran health is limited. Key informants recognize the potential for unintended consequences, such as overtreatment in VHA settings, and suggest that implementation of P4P in the community focus on relationship building and target areas such as documentation and coordination of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…However, Petersen et al [23] found that effects for group-level incentives were weaker. This was supported by Kondo et al [25], who also stated that physician-level incentives were more effective. A possible explanation was provided by Petersen et al [23], who argued that this might be because the link between individual performance and the incentive is less direct in the group-level context.…”
Section: Influence Of Application Level (Group Vsmentioning
confidence: 72%
See 4 more Smart Citations
“…However, Petersen et al [23] found that effects for group-level incentives were weaker. This was supported by Kondo et al [25], who also stated that physician-level incentives were more effective. A possible explanation was provided by Petersen et al [23], who argued that this might be because the link between individual performance and the incentive is less direct in the group-level context.…”
Section: Influence Of Application Level (Group Vsmentioning
confidence: 72%
“…The other reviews explicitly included “provider groups” in their analyses, but only some differentiated between individual- and group-specific incentives, which provides less reliable results for interpretation. Petersen et al [ 23 ], Van Herck et al [ 24 ], and Kondo et al [ 25 ] included the incentive level (individual vs. group).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations